Catch up: developing countries in the world economy - Deepak Nayyar (Oxford University Press, 2013)
This book is about the evolution of developing countries in the world economy situated in its wider historical context, spanning centuries, but with a focus on the period since the mid-twentieth century. It traces the rise and 'catch up' of the developing world and the shift in the balance of power in the world economy.